Dwelling with Design. (2nd January 2017) - Paavilainen, Heidi; Ahde-Deal, Petra; Koskinen, Ilpo
Abstract: Most studies of design focus on designers in their studios, in industry or in the commercial phase of design. In contrast, this paper looks at what happens to design after it leaves the shop. The paper reviews literature on art and design in everyday life, builds on Herbert Blumer's interactionism, and reports the key results of a longitudinal study done between 2004 and 2007 in Helsinki, Finland. It describes how people define design, how they relate to it, and how their definition of their home creates the environment in which design is either foregrounded or backgrounded.